BROAD BAND MODELLING OF ELECTROMAGNETIC WAVE COUPLING TO SCATTERERS INSIDE A METALLIC CAVITY - Hagen, J. V. (Applied Computational Electromagnetics Society Journal (ACES), 2022)
In this paper we present an approach based on the method of moments for the solution of an electromagnetic compatibility problem. We determine the results of the impact of an electromagnetic wave on metallic housings with small holes. By separating the interior and the exterior of the housing we are able to use the Green’s functions of the cavity. The number of unknowns is therefore reduced compared to solutions using the free space Green’s functions. Different sets of functions (either local or global) are used for the method of moments (MoM). Furthermore, we present a method to generate broad band data from only a few computations by using an “intelligent” interpolation procedure. Finally, we present an experimental setup and compare our computations with measurements.